Methylene Blue Removal Using Palm Oil Mill Effluent Sludge-Derived Adsorbent - Roslan, F.A.S. (Italian Association of Chemical Engineering - AIDIC, 2022)
Textile industries release a large amount of dye effluent into the wastewater that can cause health issues and endanger aquatic animals. In this study, sludge derived biochar (SB) adsorbent was produced from sewage sludge to remove methylene blue (MB) dye from wastewater. The surface area and porosity of SB are analysed by using Field Emission Scanning Electron Microscope (FESEM) and Surface Area and Pore analyser (SAP). The factors that affect the adsorption of MB in aqueous solution with SB adsorbent in batch mode are adsorbent dosage (0.5g, 1g), initial MB concentration (50 â 250 mg/L), and contact time (0 â 120 minutes). The Langmuir isotherm model fits the adsorption equilibrium results, and the pseudo-second-order kinetic model best describes the sorption kinetics of MB. The maximum adsorption capacity of MB decreases from 15.37 mg/g to 8.61 mg/g as the adsorbent dosage increases from 0.5 g to 1.0 g and contact time increases from 45 minutes to 60 minutes. Hence, sludge derived biochar is an effective adsorbent for the removal of MB dye from wastewater. Copyright Â© 2022, AIDIC Servizi S.r.l.